Urine retention in cattle putatively associated with injection of an ivermectin and closantel anthelmintic formulation into the ischiorectal fossa. Issue 3 (4th May 2019) - Castillo-Alcala, F; Brown, S; Crawshaw, T; Laven, RA; Riddle, G; Lizarraga, I
ABSTRACT: Case History: A group of 39, 19–22-month-old Friesian bulls were administered an ivermectin/closantel anthelmintic via intended S/C injection in the ischiorectal fossa on 15 June 2017 (Day 0). Over the next 50 days, 22 affected bulls presented various degrees of anorexia, abdominal pain and urine dribbling. Seventeen bulls were examined by transrectal ultrasonography which revealed urinary bladder distension in all 17, and peritoneal fluid accumulation in some. Overall, eight bulls died or were subjected to euthanasia. On-farm postmortem examination of three bulls revealed urinary bladder rupture. Clinical Findings: On Day 50 one affected live bull was admitted to Massey University for further investigation. This bull continuously dribbled urine and had an overtly distended urinary bladder as determined by rectal palpation and ultrasonography. Pathological Findings: Postmortem examination of this bull revealed a markedly distended urinary bladder, massive subcapsular and pericapsular renal oedema with retroperitoneal fluid accumulation, minimal hydronephrosis and no evidence of mechanical urinary outflow obstruction. The right ischiorectal fossa contained multifocal areas of tissue fibrosis that extended into areas innervated by the distal cutaneous branch of the pudendal nerve and the pelvic nerve. Histopathological changes consisted of extensive fibrosis, myonecrosis and neurodegeneration, and evidence of granulation tissue and inflammation at the putative injection site and in surrounding tissues. Diagnosis: A local inflammatory reaction at the presumed injection site together with localised peripheral neurodegeneration and myelopathy may have led to detrusor-sphincter dyssynergia causing urine retention. Clinical Relevance: These cases of urine retention and bladder rupture in cattle were of putative iatrogenic origin. Veterinarians should be aware of this rare complication after S/C injections in the ischiorectal fossa.